Trastornos de ansiedad en la infancia - Bragado Alvárez, Carmen (Análisis y Modificación de Conducta, 1992)
In this paper a review is mude of tlte main contributions of Behavior nlerapy to fhe treatment of Anxiefy Disorders in childhood. After reviewing the clasification of tllose following DSM-ZII(R), the main results of behavioml techniques in these cases are presented. The conclusisions of the main results in the Spanish publications are presented as well, artd suggestions for the future researclt are also offered.